Políticas territoriais do turismo: investimentos no Polo Costa dos Coqueirais em Sergipe, Brasil - Santos, Mary Nadja Lima (2009)
Political territorial dispute underlie in great proportions the universe of knowledge and the power comprised by both the State and the market. They determine space, protect the territory (sovereign) however, they (de)territorialize whenever their interests are at game. The globalized world context converges to the local, except when this territory itself produces the capital which the system rules. Therefore, this research is located in the Northeast of Brazil, particularly at Polo Costa dos Coqueirais region, in Sergipe’s coast cut by rivers, with 163km of beaches, dunes and its unique vegetation composing, through its landscape and territory identity, perspective to social, economic and environmental development. This research aims at analyzing the tourism public territorial policies and the role of the State in the investments at Polo Costa dos Coqueirais’ in order to reduce poverty in Sergipe within the two last decades. This study is supported by the methodological hermeneutic principles, participativeresearch type, which is complemented by socioeconomics (quantitative) analysis instruments. There is underlying this choice the dimension of phenomenology complement that defines the path to be followed. This definition allowed to develop not only the strategies to elaborate workshops, notebooks to gather document and field data; but also make use of forms and interviews scripts to compose the workshops results. Besides that cartograms were built to gather quantitative data in order to support this study. The substantiation of this thesis consolidates into the following prior premises: ideological (State and Market); the ones that represent tourism society (Polo Council) and pragmatic (community participation). As a result of this relation emerge: (i) International agencies’ methodology, especially BID,that has not been contributing to generate new achievements that lead to better income indicators to the population affected. Fact that corroborates with the argument that the State’s engagement with the social welfare and the lack of effective involvement of the society at conducting tourism territory policies broaden the contradictory effects of tourism investments in the Northeast by great investors; (ii) The bases for support and negotiation of those who represent the Polo’s civil society appear contradictory as this influence in public tourism policies efficiency, society does not keep its management power and this affects the advances which were obtained by participation in tourism development. (iii) Investments in tourism have caused different impacts over distinct communities that make Polo Costa dos Coqueirais. PRODETUR/SE partially accomplishes what has been established by the resource investment program of the multilateral agencies, especially concerning to BID, privileging the market itself, once it is noticeable that there was some distinct improvement between coast regions, in terms of tourism facilities to the South–Center part of the State. Thus, this study advances into proposing a territory matrix of community tourism which embodies the effective citizenship exercise as an essential element to establish, in local scale, a new project to develop tourism activities in order to contribute to overcome poverty .